Breakage and propagation of the stony coral Acropora cervicornis - Tunnicliffe, Verena (1981)
Populations of the staghorn coral, Acropora cervicornis, often form dense monotypic stands on shallow Caribbean reefs. This coral species has a fragile structure that results in large numbers of broken branches and toppled colonies, especially in high wave activity. Although more than 80% of the corals in the studied population were broken from their bases, most had become reanchored to regrow rapidly. There is little evidence of sexual reproduction, and it appears that this coral has come to dominate much of the Jamaican reef community by propagation through fragmentation.